UV Dose Governs UV-Polymerized Polyacrylamide Hydrogel Modulus - Saahil Sheth; Era Jain; Amin Karadaghy; Sana Syed; Hunter Stevenson; Silviya P. Zustiak (International Journal of Polymer Science)
Polyacrylamide (PAA) hydrogels have become a widely used tool whose easily tunable mechanical properties, biocompatibility, thermostability, and chemical inertness make them invaluable in many biological applications, such as cell mechanosensitivity studies. Currently, preparation of PAA gels involves mixtures of acrylamide, bisacrylamide, a source of free radicals, and a chemical stabilizer. This method, while generally well accepted, has its drawbacks: long polymerization times, unstable and toxic reagents, and tedious preparation. Alternatively, PAA gels could be made by free radical polymerization (FRP) using ultraviolet (UV) photopolymerization, a method which is quicker, less tedious, and less toxic. Here, we describe a simple strategy based on total UV energy for determining the optimal UV crosslinking conditions that lead to optimal hydrogel modulus.